Sosialisasi dan Simulasi Mitigasi Bencana Gempa Bumi Untuk Anak Sekolah Dasar Leuwilaja III di Sindangwangi, Majalengka, Jawa Barat - Rahmasari, Vania; Tidak ada, Sri Rum Giyarsih (Direktorat Pengabdian kepada Masyarakat, 2024)
Leuwilaja Village, Sindangwangi Subdistrict, Majalengka Regency is one of the areas in West Java that has considerable earthquake potential. Majalengka Regency has a high potential for earthquakes because it has more than 20 faults. A fault is a fracture between two blocks of rock that can move. Therefore, these faults can move at any time and trigger earthquakes in the area. One way to deal with the potential for a large enough earthquake is disaster mitigation. Disaster mitigation can be in the form of socialization to the surrounding community in order to reduce the risk of disasters, especially earthquakes. In the real work lecture activities, socialization activities are carried out which aim to implement mitigation so that the risk of earthquakes can be reduced. Socialization activities are carried out to foster an attitude of responsiveness to natural disasters from an early age and packaged with science that is easily accepted. This is done as a form of risk prevention due to a potentially large earthquake disaster. The target of this socialization activity is elementary school children as a form of prevention of child disaster victims. The method of implementing this activity is by socializing to Leuwilaja III Elementary School students in the form of knowledge about earthquakes and also how to deal with these disasters. Socialization activities are carried out by carrying out the concept of learning while playing which is marked by singing along with the song presented about the socialization material. The targets of this activity were students of SD Leuwilaja III grades 5 totaling 30 students. The results of the socialization activities are (1) the students' understanding of the things that must be done when an earthquake occurs and 90% of the students can understand the socialization material presented (2) the students look enthusiastic and happy during the socialization.